Risk of Guillain-Barré syndrome following herpes zoster, United States, 2010-2018 - Tara C. Anderson; Jessica W. Leung; Rafael Harpaz; Kathleen L. Dooling (Taylor & Francis Group, 2021)
Epidemiologic data regarding the risk of Guillain-Barré syndrome (GBS) following herpes zoster (HZ) are limited. We conducted a self-controlled case series analysis using two large national data sources to evaluate the risk of GBS following HZ among U.S. adults. We analyzed medical claims from the IBM® MarketScan® Commercial Claims and Encounters (persons 18-64 years during 2010-2018) and Centers for Medicare and Medicaid Services Medicare (persons ≥65 years during 2014-2018) databases. HZ cases were defined as persons with an outpatient claim with a primary or secondary ICD-9 or ICD-10 diagnostic code for HZ. GBS cases were defined as persons with an inpatient claim with a principle diagnostic code for GBS and an associated procedural code. We compared the rates of GBS following HZ in the 1-42-day risk window versus primary (100-365-day) or secondary (43-99-day) control windows. We identified 489,516 persons 18-64 years of age and 650,229 persons ≥65 years of age with HZ, among whom 11 and 41, respectively, developed GBS 1-365 days following HZ. The risk of GBS following HZ was increased during the risk window as compared to the primary control window for both groups, with a rate ratio of 6.3 (95% CI, 1.8-21.9) for those 18-64 years and 4.1 (95% CI, 1.9-8.7) for those ≥65 years. This study provides new and methodologically rigorous epidemiologic support for an association between HZ and GBS, and useful context regarding the benefits versus potential risks of zoster vaccination.